Depression after childbirth among mothers with obstetric complications in King Chulalongkorn Memorial Hospital. - Youngdee , K.; Roomruangwong , C. (Chulalongkorn Medical Journal, 2023)
Background : Growing evidences show that obstetric complications have a major impact on postpartum depression. However, postpartum depression and its associated factors among this population in Thailand have not been studied. Objective : We aimed to examine the prevalence of depression and association factors after childbirth among mothers with obstetric complications. Design : A cross-sectional descriptive study. Setting : King Chulalongkorn Memorial Hospital. Method Edinburgh Postnatal Depression Scale (EPDS), Personal Resource Questionnaire (PRQ-part II), and Dyadic Adjustment scale (DAS) were completed by 116 subjects during their first at 1 week (T1) and 4 - 6 weeks (T2) after delivery. The EPDS score ≥ 11 represented state of depression. Results : The prevalence of depression was 13.7% at T1 and 6.1% at T2. There were many factors associated with depression at T1 including average time of baby to sleep, body mass index (BMI) before pregnancy, BMI current, marital dissatisfaction and low social support. In the period at T2 the factors associated with depress were education level, income, delayed menarche, longer duration of labor, longer duration of baby nighttime awakening, marital dissatisfaction and low social support. Conclusion : The prevalence of postpartum depression decreased over time, from 1 week to 4 - 6 weeks after delivery. The percentage of depression was comparable to other studies with many factors related to postpartum depression. Knowing the associated factors will help the medical professionals to plan and provide appropriate assistance to the patients.